Influence of small miscuts on self-ordered growth of Ge nanoislands - Gudymenko, O.Yo.; Kladko, V.P.; Yefanov, O.M.; Slobodian, M.V.; Polischuk, Yu.S.; Krasilnik, Z.F.; Lobanov, D.V.; Novikov, А.А. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
Using high-resolution X-ray diffraction (HRXRD), we have investigated lateral ordering the nanoislands formed from Ge wetting layer of various thicknesses deposited on a strained Si₁₋xGex sublayer. We observed that the high lateral ordering degree is initiated by ordered modulation of non-uniform deformation fields. This modulation is induced by small (∼0.3°) misorientation of Si substrate from [001] direction. Finally, we show that the miscut can be the source of perfectly ordered nanoisland arrays in two dimensions when the growth is performed on the strained SiGe (001) sublayer. The effect of substrate miscut can be amplified tuning the deviation of buffer layer surface from [001] growth direction via increasing the Ge content.